2000
DOI: 10.1002/biof.5520110127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vitamin B6 contents on antibody production

Abstract: When mice were placed on diets extreme deficient in vitamin B6, ovalbumin-dependent antibody productions (IgE, IgG1, IgG2a) were significantly suppressed, and alanine aminotransferase activity in the liver was also significantly decreased. In the case of pyridoxine excess (6 mg% = about ten times standard amount) in a 70% casein diet, ovalbumin-dependent antibody productions were also considerably suppressed. These responses were weaker in a low casein (5%) or normal casein (20%) diet than in a 70% casein diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Ha et al [9] believed that high-dose PN (seven times the optimal requirement) in diets had no effect on immunocompetence in rats. However, Inubushi et al [12] pointed out that excess PN (10 times the optimal requirement) in diets was able to suppress antibody productions in rats.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ha et al [9] believed that high-dose PN (seven times the optimal requirement) in diets had no effect on immunocompetence in rats. However, Inubushi et al [12] pointed out that excess PN (10 times the optimal requirement) in diets was able to suppress antibody productions in rats.…”
Section: Introductionmentioning
confidence: 97%
“…Dietary deficiency of PN significantly decreases cell-mediated immunity, such as percentage and total number of lymphocytes, the mitogenic responses of lymphocytes in human [8], T-cell-mediated cytotoxicity in rats [9] and humor-mediated immunity, such as interleukin 2 secretion in human [8] and antibody (IgE, IgG) production in rats and chicks [10e12]. However, there is controversy about the effects of high-dose PN on immune responses in terrestrial animals [9,12,13]. Ha et al [9] believed that high-dose PN (seven times the optimal requirement) in diets had no effect on immunocompetence in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, vitamin B6 supplementation in the deficient groups resulted in the serum antibody (IgG) and anti-DNP IgE recovering to the same levels as those in the normal controls [15]. Further research showed that excessive vitamin B6 (6 mg/100 g diet) supplementation could inhibit the production of the anti-OVA antibody IgE and IgG1 due to the suppression of hepatic cathepsin B activity by vitamin B6 [16]. Therefore, a moderation of vitamin B6 might mediate immune signal transduction or regulate immune cell differentiation and cytokine production together with other signal molecules to reach an immune homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have demonstrated the effects of dietary protein deficiency on lymphocyte blastogenesis involving antigen-specific reactions such as those expected in ova-immunized pregnant mice. However, ovalbumin immunization of nonpregnant mice fed a pyridoxine supplemented diet decreases the production of several subgroups of antibodies (Inubushi et al, 2000) and a limitation on parity, correlated with high titers of autoantibodies amplified by alloantigens, has been demonstrated in ova-immunized mice (Lou et al, 1996).…”
Section: Discussionmentioning
confidence: 97%